Colton 911 : secret alibi - Cornelison, Beth (Harlequin romantic suspense, 2021)
When Valerie Yates and Nash Colton reunite, they don't expect their love could awaken old demons. Soon after Valerie confesses a devastating truth, Nash is arrested for murder. She's determined to prove his innocence but doing so means uncovering even more heartbreak and betrayal. Can the former loves find their second chance... and capture a killer tracking Nash's every move?